2020
DOI: 10.3389/fnagi.2020.585988
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Innovative Cognitive Treatment and Telerehabilitation on Subjects With Mild Cognitive Impairment: A Multicenter, Randomized, Active-Controlled Study

Abstract: Background In recent years, the potential usefulness of cognitive training procedures in normal aging and mild cognitive impairment (MCI) have received increased attention. Objective The main aim of this study was to evaluate the efficacy of the face-to-face cognitive virtual reality rehabilitation system (VRRS) and to compare it to that of face-to-face cognitive treatment as usual for individuals with MCI. Moreover, we assessed the possibility of prolonging the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 83 publications
1
44
0
2
Order By: Relevance
“…Currently, many efforts are now focused on the treatment of subjects recovering from COVID-19 ( 71 74 ), but it seems extremely important to implement TR protocols also in non-COVID subjects in various settings of neurological care, in order to provide a continuity of care during this pandemic contingency and possibly in the future ( 75 78 ). During the COVD-19 pandemic, we have tested an innovative TR approach for the remote treatment of cognitive deficits in neurodegenerative diseases ( 79 , 80 ) called HomeCoRe (Home Cognitive Rehabilitation) ( 81 ). HomeCoRe is a patient-tailored intervention stimulating many cognitive abilities, which is the home-based version of a previously tested computer-based cognitive training program (CoRe) ( 82 85 ), devised for the hospital setting.…”
Section: Telemedicine At the Time Of Covid-19mentioning
confidence: 99%
“…Currently, many efforts are now focused on the treatment of subjects recovering from COVID-19 ( 71 74 ), but it seems extremely important to implement TR protocols also in non-COVID subjects in various settings of neurological care, in order to provide a continuity of care during this pandemic contingency and possibly in the future ( 75 78 ). During the COVD-19 pandemic, we have tested an innovative TR approach for the remote treatment of cognitive deficits in neurodegenerative diseases ( 79 , 80 ) called HomeCoRe (Home Cognitive Rehabilitation) ( 81 ). HomeCoRe is a patient-tailored intervention stimulating many cognitive abilities, which is the home-based version of a previously tested computer-based cognitive training program (CoRe) ( 82 85 ), devised for the hospital setting.…”
Section: Telemedicine At the Time Of Covid-19mentioning
confidence: 99%
“…VR therapy has been tested to improve cognitive abilities in people suffering from Alzheimer's disease, Parkinson's disease, trauma or after a stroke, among others [6,49,57]. Similarly, other psychiatric pathologies have been treated, as well as dementia, eating disorders and phobias [46,52,58].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the application of VR in telerehabilitation is a new trend, the implementation of which has been accelerated by the COVID-19 pandemic. It is important to highlight that in synchronous sessions (real-time) a high interaction is achieved, while in asynchronous sessions this depends on the patient's commitment [58].…”
Section: Resultsmentioning
confidence: 99%
“…Virtual reality is one of the technologybased non-pharmacological interventions that can be used to help elderly patients with cognitive disorders. Research conducted by Manenti et al (2020), showed that a significant increase in memory, language and visual construction abilities after the end of treatment using a face-to-face virtual reality-based cognitive rehabilitation system compared to the usual face-to-face cognitive treatment.…”
Section: Results and Analysissmentioning
confidence: 99%
“…Research conducted by Manenti et al (2020) said that cognitive rehabilitation techniques using virtual reality can improve several aspects of cognitive function such as memory, language, and visual construction abilities. In assessing cognitive function, there are several indicators which include orientation, language, attention, calculation, memory, construction, and reasoning (Polidori et.…”
Section: Discussionmentioning
confidence: 99%